2012
DOI: 10.1097/prs.0b013e31825dbff3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Pooled Analysis of Peroneal Artery Perforators for Fibula Osteocutaneous and Perforator Flaps

Abstract: This systematic review and pooled analysis of all available and complete peroneal artery perforator data demonstrates clustering over the 0.6 interval of the lateral leg. This interval should be considered during flap design and elevation to reliably capture irrigating perforators for free and local flap applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…The peroneal artery perforators did not show this positive correlation with leg length, because the peak incidence area of peroneal artery perforators was at the diaphyseal area. Iorio et al, 12 in their systemic review that investigated 445 legs and 1710 perforators, also found a centrally located unimodal distribution of peroneal artery perforators.…”
Section: Plastic and Reconstructive Surgery • May 2016mentioning
confidence: 93%
See 1 more Smart Citation
“…The peroneal artery perforators did not show this positive correlation with leg length, because the peak incidence area of peroneal artery perforators was at the diaphyseal area. Iorio et al, 12 in their systemic review that investigated 445 legs and 1710 perforators, also found a centrally located unimodal distribution of peroneal artery perforators.…”
Section: Plastic and Reconstructive Surgery • May 2016mentioning
confidence: 93%
“…[7][8][9][10][11][12][13][14][15] However, even if we could locate an appropriate perforator accurately, it is not possible to make an exact estimate of the maximum area or width-to-length ratio of a specific perforator.…”
mentioning
confidence: 99%
“…According to a recent overview, the most reliable perforator is located at the transition of the middle and distal thirds. 30 Nevertheless variations are always possible, which makes the inclusion of the peroneal vessels necessary if the calibre of the perforators seems too small for a direct anastomosis.…”
Section: Soleus Perforator Flapmentioning
confidence: 99%
“…A systematic review revealed that the number of perforators over the lateral leg ranged from 3.58 to 7.57. 20 Yu et al 21 showed that the perforators clustered over the proximal third of the fibula were primarily musculocutaneous (84%), whereas another group, over the distal third, was primarily septocutaneous (96%), with 1 to 3 perforators present simultaneously. The proximal musculocutaneous perforator could not always be traced back to the peroneal vessel pedicle, in contrast to the septocutaneous perforator.…”
Section: Discussionmentioning
confidence: 99%